EFEKTIVITAS PROGRAM GERHAN PADA LAHAN TEMBAKAU DI LERENG SUMBING DAN SINDORO - , Aulia Nur Umiyati ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Forest and Land Rehabilitation Action (Gerhan) is a Government program aimed to improve the quality of environment on marginal lands through revegetation techniques with annual crops. Revegetation techniques are considered contrary to the pattern of tobacco use land-based agricultural crops has been done since the time of Cultuurstelsel. This is because the nature of tobacco is not tolerant of annual crops. One measure of Gerhan effectiveness is physical and non-physical output (social acceptance). Social acceptance was measured through the strengthening of social values, changing attitudes and participation of target groups for land rehabilitation efforts. This study aims to evaluate the Gerhan effectiveness and to describe the factors that influence the effectiveness. Research carried out on tobacco land at sumbing and sindoro mountainsides, Temanggung District. Determination of the location of the sample performed in 6 purposively on Gerhan Farmer Group in 2004 with 168 respondents. The method used was qualitative and quantitative deductive. Information result obtained with the technique of triangulation that is interview, observation and questionnaires. Gerhan program on tobacco land at Sumbing and Sindoro mountainsides effectively reduce the critical land, increasing private forest area and to promote social acceptance. The social acceptance appear on strengthening social values in society are actualized through the change of attitude so as to encourage public participation in efforts to accelerate the rehabilitation of degraded lands. Spatial, situational and social context